Ferdinand Hillers Jugendsymphonie in e-Moll: Zu ihrer Entstehung und Identifizierung - Kim, Jin-Ah (Die Musikforschung, 2023)
This brief article discusses the genesis and identification of Ferdinand Hiller’s Youth Symphony in E minor. In contrast to previous research, it is argued that the “third” Symphony in E minor (September 1831) is not a completely new work, but a heavily revised new version of the Symphony in E minor (September 23, 1829). This hypothesis can be substantiated with Hiller’s entries in his own handwritten catalogue of works as well as autographs or copies of the work, which show that he revised the first and second movements, replaced the third movement and arranged a “Chant des Pirates” as finale. A passage from a letter by Felix Mendelssohn Bartholdy, who had offered to perform Hiller’s symphony in Leipzig, confirms the thesis.